ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN ORGANISASI NIRLABA FINANCIAL STATEMENT ANALYSIS TO EVALUATE FINANCIAL PERFORMANCE OF NON-PROFIT ORGANISATIONS - Kurniawan, Muchamad Rizqy; Kirana, Nanda Wahyu Indah (LPPM Universitas Bina Bangsa, 2024)
The mosque is a house of worship for Muslims to do prayer. The majority of the Mosque's funds come from community donations. The use of these funds requires a financial report as evidence of responsibility. Analysis is needed to explain the performance of the mosque management using financial statements. This study was conducted to determine the good or bad performance of the mosque from the results of the analysis of financial statements. The aspects evaluated of the mosque's performance are fiscal performance, public support, and fundraising efficiency. The method used for this research is a qualitative method with data collection performed by observation and interviews to mosque management. The object of study used is the mosque's financial statements for the years 2022 and 2023. The results of the analysis show that the financial performance in the year 2022 and 2023 is quite good. Some of the ratios studied in 2022 were obtained better than in 2023. The results of this study indicate that the mosque management must make improvements in order to be more efficient in obtaining revenues from other sectors